Tantangan Teknologi Informasi Perspektif Hukum Islam - Herman, Muhammad Akbar; Gassing, Qadir; Rahman R, Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The objective of this research is to understand the impact of information technology on human life, the challenges faced by Islamic sciences in response to technological advancements, and the use of information technology from the perspective of Islamic law. The findings of the research indicate: 1) The positive impact of information and communication technology is the ease of conducting buying and selling activities through e-commerce or online trading thanks to the internet. One example of the negative impact of information and communication technology is the increasing difficulty in protecting children from harmful content on the internet; 2) The factors that challenge Islamic sciences in the midst of modern scientific developments include the ambivalence of technology, the fact that many Muslims still emphasize textual studies over the study of sociocultural realities, and the lack of a clear paradigm regarding the position of normative values, the existence, and the scientific structure of Islam; 3) Islam does not recognize the division of human life into separate fields, so the development of information technology is also an integral part of a Muslim’s holistic life, which must be oriented toward the paradigm of tawhid (monotheism). Mastery of information technology and its optimal use are important for every Muslim as a means to draw closer to the Creator. Therefore, the application of technology should align with Islamic teachings and values and be dedicated to upholding human values..